The Shooting Star : Growing up on the Spokane Indian Reservation, - Wynecoop, Arnold, 1934-
One photocopied and bound autobiographical manuscript by Arnold 'Judge' Wynecoop entitled "The Shooting Star: Growing Up on the Spokane Indian Reservation." The manuscript is 111 pages and contains many photographs as well as stories. In the foreword, Wynecoop writes "the seven Wynecoop sons were part of a close-knit Indian family living on a reservation during back-to-back eras of the Great Depression and WWII." The manuscript includes many family stories of growing up on the reservation. It also includes descriptions of working as a logger and a miner in small scale mining operations. Many of the stories, which are not in chronological order are about his childhood, and include stories about hunting and fishing as well as family life. The manuscript also includes a family tree.